Generasi Milenial Sebagai Calon Pemimpin Masa Depan Dalam Perspektif Nilai-Nilai Pancasila - Agus Muhammad Barkah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research is about how to see the strengthening and efforts to maintain and implement the values of Pancasila and make the values of Pancasila an important value for the life of the Indonesian nation, and also related to equipping the millennial generation as a potential recipient of the nation's leadership relay in the future, especially in the era of the Golden Indonesia 2045. The cultivation of Pancasila values in every generation, including the millennial generation, is very important because it can be decisive in efforts to advance the Indonesian nation into a developed nation and produce superior generations. This research uses a qualitative method by examining literature studies and referring to existing situations and conditions in Indonesia that occur in the formation and awareness of the millennial generation in the values of Pancasila.